Eksplikasi Konsep Milku Al-Yamīn Dalam Al-Qur’ān Dengan Hubungan Seks Non Marital Kajian Tafsir Tematik - Imran, Maizul (LPPM Sekolah Tinggi Ilmu Al-Qur'an Wali Songo Situbondo, 2022)
Abstract: The research purposed to find out the concept of milku al-yamīn in the Koran, whether it means an alternative sexual channeling or is it a description of the tradition that occurred in the Arab society before Islam. Research conducted by Muḥammad Syaḥrūr as the validity of non-marital sexual relations shows that understanding the meaning of milku al-yamīn in this contemporary era is a contract between a man and a woman to have sexual intercourse. With the results of his research, it raises the pros and cons and problems in Indonesian society. In connection with bridging and deepening the meaning of milku al-yamīn in the Koran through a thematic interpretation approach. In conclusion, the meaning of milku al-yamīn is that of a slave girl who is obtained through war, excluding its meaning from other ways. While the ability to associate with them is not for an outlet of sexual desire, but historically as an attempt to elevate the status of slaves to the equivalent of freedom. This concept can be considered as an alternative to fight discrimination against people accused of adultery.